The effect of gamification on the medication knowledge, performance and satisfaction of nurses in continued medical education: A quasi-experimental study - Raziyeh Ghafouri; Shiva Ghasemniaye Namaghi; Banafshe Khoshgoui (PLoS ONE, 2025)
Background and objective One of the primary challenges within the health system is improving nurses’ motivation and attitude toward participation in the continuous education program. This study was conducted aim to investigate the effect of gamification on medication knowledge, performance and satisfaction of nurses in continued medical education (CME). Methodology The study was conducted as a quasi-experimental design from November 1, 2022, to February 1, 2024. Participants were 128 nurses with a minimum of 6 months of work experience who were randomly assigned to two groups, intervention and control groups via a colored card. Baseline assessments of medication knowledge and drug administration practices were conducted one week prior to the intervention. Education in both groups consisted of five 2-hour sessions. In the control group, education was delivered using the lecture method, while in the intervention group, the competitive software (Kahoot!) was used. One week after the completion of the training sessions, participants’ knowledge, drug administration skills, and satisfaction were evaluated. Results The participants’ average (standard deviation) age was 30.34 (5.34), with 49 male (38.35%) and 79 female (61.7%). Wilcoxon signed-rank test results demonstrated statistically significant difference in the knowledge and performance within both groups (p < 0.001). Mann-U-Whitney test findings revealed a significant difference between the two groups of participants in performance and satisfaction with the educational approach education (p < 0.001). Conclusion The gamification method enhanced nurses’ satisfaction and medication performance. Using Kahoot as a game-based competitive application has been shown to enhance nurses’ knowledge of pharmacology as well as increase participants’ satisfaction with educational programs. Therefore, it is recommended that nursing educators and administrators integrate gamified approaches and strategies—such as Kahoot!—to enrich learning experiences and motivate participation in ongoing professional development.